The Design And Build of Telemetry system Portable Ground Control Station (GCS) as Control and Monitoring on Unmanned Aerial Vehicle (UAV) Aircraft Galak-24 - Ghofur M., Abdul; Darmawan, Yudhi; Ridwan, Muhammad (Pustaka Poltekad, 2021)
Abstract – Ground Control Station (GCS) is a very important part in controlling and monitoring UAV aircraft as well as monitoring a mission so that operators at the home base can send mission orders. The importance of this mission requires a system in this case, namely the GCS that can be connected to various types of unmanned vehicles. This study develops a GCS system that is used for controlling and monitoring the condition of UAV aircraft and sending waypoint tracking mission commands that are connected to a cloud server via the internet. This system consists of two units, namely the flight unit and the video unit, the flight unit consists of a flight controller, the video unit is a system that is on a camera connected to telemetry and connected to the internet so that it can be accessed via the internet, thus controlling and monitoring UAV aircraft and target control delivery on the GCS will be accessible anywhere via the internet. The GCS system has been able to display the condition of the aircraft status, sending flight hover mission commands, land and sending missions, namely tracking waypoints and camera object coordinates. In areas where the mission's 4G internet signal can run smoothly by sending 15 takeoff and landing control waypoints which manually with precision results, the fix wings type UAV aircraft can pass through several tracking waypoints that experience errors.